Redescription of Sillago (Parasillago) indica McKay, Dutt & Sujatha, 1985 (Perciformes: Sillaginidae), with a reassignment to the subgenus Sillago - Kaga, Tatsuya; Ho, Hsuan-Ching (Zootaxa, 2012)
The Indian sillago, Sillago indica McKay, Dutt & Sujatha, 1985, is redescribed on the basis of three paratypes and two newly collected specimens.  The presence of two posterior extensions of the swimbladder instead of one suggests that it belongs to the subgenus Sillago.  Comments on its subgeneric status and comparisons with members of Sillago (Sillago) are provided.  Two specimens collected from Vietnam represent the first record of the species from the South China Sea, western Pacific Ocean.